COLLECTIVE DEFENSE – A MEANS TO ACHIEVE A MORE SUSTAINABLE FUTURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The report analyzes the geopolitical situation in the world at the beginning of 2025. NATO is entering its eighth decade as a successful military-political alliance but faces new threats, which we will examine in this study. The conflict between Russia and Ukraine highlights the need for adaptation, deterrence, and innovation. NATO’s Strategic Concept until 2022 reaffirms its commitment to unity and security. This study uses the Thomas L. Saati and  Lotka–Volterra equations for security analysis, identifying key dependencies in the changing landscape. It outlines five main challenges: adapting NATO and the EU to new threats, modernizing military systems, prioritizing military security in Bulgaria, increasing the military budget by 2027, and emphasizing collective defense for European resilience. An interdisciplinary approach is crucial to address these challenges effectively.